Progress in Spinel‐Structured Cobaltite‐Based Positive Electrode Materials for Supercapacitors. Issue 26 (8th July 2022) - Dhandapani, Preethi; Maurya, Dheeraj Kumar; Angaiah, Subramania
Abstract: In recent days, the family of spinel cobaltites with multiple oxidation states has received much attention as an electrode material for supercapacitors. Profiting from its superior electrochemical performance, these cobaltites play a significant role in energy storage and conversion devices. In this review, we provided an in‐depth description of spinel cobaltites. Further, we review several cobaltites and their composites, corresponding synthesis methods, and the application of these materials for supercapacitors. As a result of several extraordinary outputs, spinel cobaltites are likely to be widely studied in the future. Abstract : The multi‐oxidation states in spinel‐structured cobaltites serve as excellent electrode materials for supercapacitors. This review revitalizes the progress of existing cobaltites and their composites, corresponding synthesis methods, influencing parameters and strategies to improve the electrode performance, and the current research developments are critically summarized. Based on the ongoing development, a future outlook for enhancing the performance of the electrode materials is highlighted.